The Effect of Leverage on Bidding Behavior: Theory and Evidence from the FCC Auctions - Clayton, Matthew J.; Ravid, S. Abraham (Review of Financial Studies, 2002)
This paper investigates how firms’ bidding behavior in various auctions is affected by capital structure. A theoretical model is developed where the first price sealed bid and the English auction are examined. We find as debt levels increase, firms tend to decrease their bids. The lower bids give the competition incentives to decrease their bid as well. These results are then investigated empirically using the recent FCC spectrum auctions. Consistent with the theoretical model, larger debt levels of the bidding firm and the competition tend to lead to lower bids. Additional determinants of bidding behavior in these auctions are also analyzed.